Effects of the Preannouncement of Donation Expenditure on the Evaluation of Charitable Organizations and Overhead Aversion - Kwanho Suk; Triza Mudita (Asia Marketing Journal)
Charitable organizations use donated funds for program costs to support the cause and overhead costs to cover the charity's general operation and fundraising. This research investigates the influence of preannouncement of donation expenditure on attitudes toward charity and overhead aversion (i.e., negative response to overhead). Preannouncement of donation expenditure involves the disclosure of how donor contributions will be allocated to the program and overhead costs. The results of two empirical studies show that preannouncement positively influences attitudes toward charity and mitigates overhead aversion. Study 1 indicates that the preannouncement of donation expenditure enhances perceived donation impact, leading to a positive change in attitudes toward the charity. Study 2 shows that preannouncement on charitable organizations increases donation intentions. This research also shows that the preannouncement effect is more pronounced when the charity's overhead ratio is lower and is stronger for charities with lower credibility.